Protocol for Management of Maxillofacial Injuries Caused by Fox Attack: A Case Report - Vidya M S; Anu Jose; Sachin Aslam A; Sooraj Soman (Rajiv Gandhi University of Health Sciences, 2024)
Injuries particularly those caused by wild animals like fox are rarely reported in the literature. The sequalae following animal attacks and the algorithm for its management still remains controversial owing to limited data available in the literature. The pattern of injury caused microorganisms isolated from this wound the defect created whether it involves soft tissue or hard tissue and the feasibility and risks associated with immediate delayed closure of the wound make it a challenging case for the surgeons. These bites as per the available literature can result in tears punctures avulsions abrasions and crush injuries. Appropriate consideration should be given while evaluating the clinical presentation and determining a protocol for establishing treatment specific to that particular wound. This article describes the management of fox attack injury in a 66 year old male patient.